Length-weight relationships and growth pattern of Macrobrachium malcolmsonii (H. Milne-Edwards, 1844) from the river Old Brahmaputra, Bangladesh - Dipankar Paul; Mst. Tasnima Khatun; Md. Taskin Parvez; Shahroz Mahean Haque; Zoarder Faruque Ahmed (Journal of Fisheries, 2021)
Study of biological parameters of a species is important for its sustainable management. The length-weight relationships and growth patterns of Macrobrachium malcolmsonii (H. Milne-Edwards, 1844), collected from the river Old Brahmaputra in Bangladesh, were determined in this study based on 359 specimens (carapace length, CL: 11–90 mm; body weight, BW: 0.2–54.4 g) including 308 male and 351 female individuals. For both sexes, intercepts, slopes, and coefficients of determinations of regression analyses between CL and BW varied monthly. The lowest values of intercept (–11.51 and –11.65 for male and female respectively) was recorded in October whereas the highest values were recorded in January for male (–7.01) and March for female (–8.26 for female). The minimum coefficient of determination was 0.784 (for male) and 0.801 (for female) whereas the maximum coefficient of determination was recorded 0.971 (for male) and 0.970 (for female). For male, the b value at 95% Cl revealed that the growth in March, June, July, September and February were isometric and in April, May, October, November and January were allometric. Whereas for female, the growth in March, April, June, July, November, January and February were isometric and was allometric in May, September and October.